The use of concrete material in teaching and learning Mathematics - Rusiman, Mohd Saifullah; Mohamad, Mahathir; Che Him, Norziha; Kamardan, Muhammad Ghazali; Othaman, Saifulnizam; Shamshuddin, Muhammad Hakim; Samah, Mansor; Aziz, Norazli (Medwell Publications, 2017)
This research is done as an approach to improve or enhance the quality of education. It is also to encourage teachers to become more aware of their own practice to be critical of such practices and to be prepared to change it. It involves teachers in the inquiry and conducted by them and other teachers involved in together. Accordingly, this study explores the effectiveness of teaching aids (concrete materials) in the teaching and learning process of mathematics in primary schools. Eighty six people from Sekolah Kebangsaan Rawang consisted of eighty three pupils year four, five and six and three teachers who taught mathematics have been selected to participate in this research. Data collections are based on questionnaires to determine the effectiveness on teaching aids that have been used in schools. Besides, the respondent's perceptions of the importance and role of teaching aids in teaching and learning of mathematics also the frequency of certain teaching aids usage. The measures used are based on the value of percentage and mean. The result shows that mathematics teachers have been using concrete materials as the main ingredient in starting a new methodology to pupils. Hopefully, they will folllld it easier to absorb any new topic after applied this approached.